SERVICESCAPE DAN PENGARUHNYA PADA PERILAKU 1 PEMBELIAN ULANG DALAM BISNIS KULINER - Eka Nasmita; Waluyo Budi Atmoko; Finisha Mahaestri Noor (Conference on Innovation in Health, Accounting and Management Sciences (CIHAMS), 2020)
This research purpose to test servicescape and effect on repeat purchase behaviour in the culinary business.Good perceived quality can increase satisfaction and repeat purchase intention so that it supports consumers to make repeat purchases behaviour. Dat a obtained through a questionnaire distributed to visitors to the Grandis Barn Surakarta. The sampling technique used was purposive sampling with a population of people in a Solo city of 200 respondents. Hypothesis testing is done by using SEM an regression analysis. The results showed that all hypotheses were supported except H1b. These results give the meaning of repeat purchase behaviour influenced by perceived satisfaction and repeat purchase intention, while perceived quality is not an important factor in influencing the repeat purchase behaviour but, perceived quality can be support consumens to repeat purchase intention.